Cost of care for preterm babies to Clients and influence of costs on care in resource limited settings – Societal perspective: A case of Jinja Regional Referral Hospital in East central Uganda - Ziyada Babirye; Elizabeth Kiracho Ekirapa; Anthony Ssebagereka; Angela Nakanwagi Kisakye; Freddie Ssengooba (Journal of Interventional Epidemiology and Public Health)
Introduction: The costs of care for preterm birth to clients and the influence of costs on preterm care remain a significant issue to the health system and families globally especially in the low-middle income countries particularly, in Asia and sub-Saharan Africa with already constrained economies. However, this has not received worthwhile attention. We estimated the costs of care for preterm babies to families (clients) and the influence of costs on the care for preterm babies from a societal perspective in Jinja Regional Referral Hospital.